2022
DOI: 10.1097/brs.0000000000004344
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Social Determinants of Health Disparities in Spine Surgery Affect Preoperative Morbidity and Postoperative Patient Reported Outcomes

Abstract: Study Design. Retrospective observational study. Objective. To elucidate racial and socioeconomic factors driving preoperative disparities in spine surgery patients. Summary of Background Data. There are racial and socioeconomic disparities in preoperative health among spine surgery patients, which may influence outcomes for minority and low socioeconomic status (SES) populations.Methods. Presenting, postoperative day 90 (POD90), and 12month (12M) outcome scores (PROMIS global physical and mental [GPH, GMH] an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…16 Previous literature has highlighted the notable variation in orthopaedic service availability, inferior outcomes, and increased risk of complications in racial and ethnic minorities. [16][17][18] African American patients report higher pain intensity scores, longer lengths of hospital stay, higher mortality rates, and lower satisfaction with their care and outcomes, compared with White patients. 17,19,20 However, the literature scarcely evaluated differences in care in Hispanics compared with other races or ethnicities.…”
mentioning
confidence: 99%
“…16 Previous literature has highlighted the notable variation in orthopaedic service availability, inferior outcomes, and increased risk of complications in racial and ethnic minorities. [16][17][18] African American patients report higher pain intensity scores, longer lengths of hospital stay, higher mortality rates, and lower satisfaction with their care and outcomes, compared with White patients. 17,19,20 However, the literature scarcely evaluated differences in care in Hispanics compared with other races or ethnicities.…”
mentioning
confidence: 99%
“…Prior studies have demonstrated that socioeconomic factors are associated with disparities in PROs completion, 45 spine patient outcomes, [46][47][48] and the elements of health measured by the PROMIS-GH instrument. 49 Thus, their exclusion from the current study represents a significant limitation of our findings. A larger, multicenter study should be performed to expand these results to other institutions and populations with larger, more varied populations.…”
Section: Health Services Researchmentioning
confidence: 87%
“…Thus, patients from low SES communities made up only 28% of our comparative group. Even after combining low SES groups together, our study may have been underpowered to detect differences across SES given the relative unequal distribution of patients that our power analysis was based on 16. Moreover, only 2.8% of patients did not have Medicare or private insurance, thus our study may not capture patients who reside within the lowest SES of their respective communities 28.…”
Section: Discussionmentioning
confidence: 99%
“…A power analysis indicated that a minimum of 780 patients was necessary for adequate statistical comparisons between DCI groups. 16 Following Institutional Review Board approval from our urban academic medical center, we retrospectively identified patients who underwent an ACDF between 2014 and 2020 using a Structured Query Language (SQL) search from Current Procedural Terminology (CPT) code 22551. All adult patients (18 years or older) who underwent primary, elective one-level to four-level ACDF procedures met inclusion criteria.…”
Section: Data Collection and Study Designmentioning
confidence: 99%